Effect of cosmetic chemical preservatives on resident flora isolated from healthy facial skin. (12th December 2018) - Wang, Qian; Cui, Shumei; Zhou, Li; He, Keke; Song, Liya; Liang, Haiyan; He, Congfen
Abstract: Background/Aims: Healthy skin harbors numerous microbes known to maintain its health and prevent attacks from external pathogens. The influence of chemical preservatives commonly used in cosmetic products on facial resident flora remains poorly characterized. In this study, we aimed to investigate the antibacterial activity of five such preservatives on in vitro cultivated skin‐resident bacteria. Methods: Both Gram‐positive and Gram‐negative bacteria were isolated on blood agar, tryptic soy agar, and nutrient agar; Gram‐negative bacteria were then selected on Hank's balanced salt solution containing antibiotics and Reasoner's 2A. The minimum inhibitory concentrations (MICs) of methylisothiazolinone (MTI), iodopropynyl butylcarbamate (IPBC), ethylhexylglycerin (EHG), methylparaben (MP), and phenoxyethanol (PE) were estimated for nine facial resident bacteria, Escherichia coli, and Staphylococcus aureus using serial broth dilution in vitro. Results: The maximum test concentrations coincided with the upper limits set by the " Cosmetic Safety and Technical Specification " (2015 edition, China). Nine facial resident bacteria were isolated from 14 healthy adults: Staphylococcus epidermidis, Staphylococcus capitis, Kocuria, Micrococcus luteus, Bacillus, Acinetobacter, Pseudomonas parafulva, Pseudomonas oleovorans, and Roseomonas cervicalis . MTI and IPBC displayed the strongest effect on all tested strains (MICs ≤0.01%), followed by EHG and MP (MICs ≤0.3%), and finally PE with the weakest effect (MIC ≤1%). Conclusion: The five chemical preservatives assayed inhibited survival of the nine facial resident bacteria isolates, when tested at the maximum allowed limit. The corresponding MICs will provide a reference for the effective utilization of these compounds in product formulations.